Acute recreational drug toxicity: Comparison of self-reports and results of immunoassay and additional analytical methods in a multicenter European case series. Issue 5 (February 2018) - Liakoni, Evangelia; Yates, Christopher; Dines, Alison M.; Dargan, Paul I.; Heyerdahl, Fridtjof; Hovda, Knut Erik; Wood, David M.; Eyer, Florian; Liechti, Matthias E.
Abstract : Abstract: The aim of the study was to compare self-reported and analytically confirmed substance use in cases of acute recreational drug toxicity. We performed a retrospective analysis of emergency department presentations of acute recreational drug toxicity over 2 years (October 2013 to September 2015) within the European Drug Emergencies Network Plus project. Among the 10, 956 cases of acute recreational drug toxicity during the study period, 831 could be included. Between the self-reported substance use and the toxicological results, the highest agreement was found for heroin (86.1%) and cocaine (74.1%), whereas inhalants, poppers, and magic mushrooms were self-reported but not analytically detected. Cathinones and other new psychoactive substances (NPS) could be detected using additional analytical methods. Among cases with both immunoassay (IA) and confirmation with mass spectrometry (MS), the results were consistent for methadone (100%) and cocaine (95.5%) and less consistent for amphetamines (81.8%). In cases with a positive IA for amphetamines (n = 54), MS confirmed the presence of 3, 4-methylenedioxymethamphetamine (MDMA), amphetamine, methamphetamine, and NPS in 37, 20, 10, and 6 cases, respectively, also revealing use of more than 1 substance in some cases. MS yielded positive results in 21 cases with a negative IA for amphetamines, including amphetamine, MDMA, methamphetamine, and NPS, in 14, 7, 2, and 2 cases, respectively. In conclusion, the highest agreement was found between self-reports and analytical findings for heroin and cocaine. The diagnosis of NPS use was mainly based on self-report. The IAs accurately identified methadone and cocaine, and MS had advantages for the detection of NPS and amphetamine derivatives. Abstract : Supplemental Digital Content is available in the text